IL-4, JAK-STAT signaling, and pain - Busch-Dienstfertig, Melanie (Landes Bioscience, 2013)
During inflammation, several mediators directly or indirectly induce pain including pro-inflammatory cytokines and there is evidence that the JAK-STAT pathway is involved in the formation of pronociceptive cytokines. The same pathway, however, is also of importance for anti-inflammatory cytokines such as IL-4 to counteract the inflammatory reaction and—as it seems based on the current literature—nociceptive symptoms. Current therapeutic approaches targeting molecules of the JAK-STAT signaling cascade are auspicious but as this review demonstrates, more experimental and clinical studies are required to decipher the specific contribution of this pathway in the modulation of pain.